Unraveling the Dynamics of Carpet Area Measurement: Implications for Real Estate Development and Urban Planning - Gourav Kumar Sharma (International Journal of Rural and Regional Development, 2024)
Real estate development and urban planning depend on carpet area measurement for property valuations, regulation compliance, and buyer’s decision-making. In the past, the absence of a standard definition of carpet area often resulted in varying calculations of area and gave the buyers a short end of the stick as a product of mistrust. In India, the introduction of the Real Estate (Regulation and Development) Act (RERA) brought in a standardized definition of carpet area, thereby creating transparency and accountability in property transactions. The notion of carpet area defined as net usable floor area within the walls of an apartment has been expanded to exclude external walls, balconies, and common areas so that a buyer is shown exactly what the actual living space shall be. For real estate development, this shift has a serious bearing on the re-designing of project designs and pricing strategies in conformity to the norms set out by RERA, and as such can impact profit margins and competitive dialectics in the industry. Standardized carpet area measurements are beneficial from an urban planning viewpoint, as they enhance accurate population density assessments, permit better land use planning, and reduce system development costs from less inaccurate infrastructure development. However, implementation challenges remain, and implementation must be faithful to the reform if it is to reap its benefits: Consistent enforcement across states and clear measurement standards are needed. RERA standardizes carpet area measurement to promote a more transparent and just realty market as well as foster an ecosystem for sustainable urban development
Keywords: Ecological Preservation; Environmental sustainability; Real Estate Development; urban planning